2018
DOI: 10.1099/jgv.0.001067
|View full text |Cite
|
Sign up to set email alerts
|

Protein–protein interactions among the structural proteins of Chilo iridescent virus

Abstract: Chilo iridescent virus (CIV), officially named invertebrate iridescent virus 6 (IIV6), is a nucleocytoplasmic virus with a ~212-kb linear dsDNA genome that encodes 215 putative open reading frames (ORFs). Proteomic analysis has revealed that the CIV virion consists of 54 virally encoded proteins. In this study, we identified the interactions between the structural proteins using the yeast two-hybrid system. We cloned 47 structural genes into both bait and prey vectors, and then analysed the interactions in Sac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Iridovirus MCP has been proved to be essential for virus replication by siRNA-based knockdown and anti-MCP serum-based neutralization test [34]. A homologue of SGIV VP57, CIV 295 L, is predicted to bind the viral DNA or DNA-binding proteins, has a function in the viral DNA replication or virus gene transcription [35]. Both SGIV VP57 and CIV 295 L have a predicted nuclear localization signal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Iridovirus MCP has been proved to be essential for virus replication by siRNA-based knockdown and anti-MCP serum-based neutralization test [34]. A homologue of SGIV VP57, CIV 295 L, is predicted to bind the viral DNA or DNA-binding proteins, has a function in the viral DNA replication or virus gene transcription [35]. Both SGIV VP57 and CIV 295 L have a predicted nuclear localization signal.…”
Section: Discussionmentioning
confidence: 99%
“…Co-transfection and luciferase reporter assays showed that the transient expression of four VATTs alone or combined did not significantly affect the activity of the SGIV ICP46 promoter without SGIV infection. The virion protein composition of five iridoviruses have been determined, including SGIV [32, 33, 3638], these studies showed that iridovirus virions contain 40 to 64 virion-associated proteins and the protein-protein interactions between virion-associated proteins are required for viral assembly and other important functions throughout the course of infection [35]. It reasonable to infer that not only the presence of four VATTs but also the protein-protein interactions and structural connection existing among VATTs were needed for the transactivation of SGIV ICP46.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different approaches, such as co-immunoprecipitation (co-IP) assays [12], fluorescence microscopy, and yeast two hybrid (Y2H), have been widely used in the investigation of protein–protein relationships or interactions [13]. Recently, the Y2H assay was used to analyze protein–protein interactions among the structural proteins of Chilo iridescent virus, a member of genus Iridovirus [14].…”
Section: Introductionmentioning
confidence: 99%